Gamma ray irradiation inhibits Plasmodium falciparum multiplication in in vitro culture supplemented with tritium labeled hypoxanthine - HARRY NUGROHO EKO SURNIYANTORO; DARLINA DARLINA; SITI NURHAYATI; DEVITA TETRIANA; MUKH SYAIFUDIN (Nusantara Bioscience, 2016)
Abstract. Surniyantoro HNE, Darlina, Nurhayati S, Tetriana D, Syaifudin M. 2016. Gamma ray irradiation inhibits Plasmodium falciparum multiplication in in vitro culture supplemented with tritium labeled hypoxanthine. Nusantara Bioscience 8: 8-13. Malaria remains a major public health threat in the world. Therefore an attempt to create malaria vaccine for supporting the control of disease was taken by attenuating parasites with gamma rays and it was proven effective based on microscopic observation. The objective of this research was to assess the effectiveness of gamma rays to attenuate malaria parasites based on isotopic method. A laboratory strain of P. falciparum (3D7) was in vitro cultured with standard procedure and it was irradiated with gamma rays at doses of 150-250 Gy and unirradiated parasites served as control. Twenty four hours after 1-2 µCi of 3H-hypoxanthine was added into culture 100 µl of medium was taken and was repeated at various times, then hypoxanthine incorporation was measured with beta counter. Microscopic observation of parasitemia in culture was also done. The results showed that there was a fluctuation in multiplication of parasites post irradiation mainly in higher dose (more than150 Gy). Irradiated of parasites were more active in incorporate with purine precursor up to 48 hours. Parasites returned to their highest activity at 116 hours after hypoxanthine addition. No significant difference was found among doses of irradiation with p of 0.05. This was quite different from the finding from microscopic observation. It was known that dose of 150 Gy was the most effective dose for inhibiting of the parasite multiplication where some factors affecting these facts.